A study on the effect of using the video teach-back method in continuous nursing care of stroke patients - Wang, Fei; Feng, Wen-Ming; Zhu, Ming; Sun, Qi; Zhang, Yong-Mei; Wang, Bing; Luo, Xiao-Yong; Shen, Jian-Tong; Fang, Xiao-Wei; Zhang, Ting; Cui, Ge (Frontiers in Public Health, 2024)
Objective To explore the effect of a video teach-back method on continuous family nursing care of stroke patients. Methods Stroke patients hospitalized in our hospital between March 2020 and March 2023 who met the inclusion criteria were randomly divided into an intervention group (n = 45), who received routine health education plus video teach-back training of caregivers, and a control group (n = 45), who received routine health education only. The effects on nursing-related variables were compared between the two groups. Results Total scores representing the caring ability of caregivers in the intervention group increased significantly over time relative to baseline and were higher than those of the control group. Scores representing the care burden of caregivers in the intervention group decreased significantly over time and were lower than those of the control group. Conclusion The teach-back method combined with video education improves the nursing ability of family caregivers and can improve the self-care ability of stroke patients.